THE CONCEPT OF HUMANISM AND AN ENLIGHTENED SOCIETY IN “RASHAHOTU AYNIL-HAYOT” (Scientific journal of the Fergana State University, 2026)
This article provides a philosophical analysis of the ideas of humanism presented in “Rashahotu Aynil-Hayot” and their significance in building an enlightened society. The work highlights the concepts of spiritual purification, moral perfection, and the establishment of social harmony based on Sufi philosophy. These ideas are of great relevance in the modern era of globalization, where the preservation of human dignity, spiritual awakening, and social justice are of utmost importance. The study interprets “Rashahotu Aynil-Hayot” as a source of spiritual renewal, intellectual freedom, and the formation of a harmonious and perfect individual.